Adequabilidade das áreas de vegetação ripária da microbacia do Córrego Comur - Botucatu (SP) em função da legislação ambiental - Moreira, Katiuscia Fernandes [UNESP]; Pissarra, Terreza Cristina Tarlé [UNESP]; Millani, ThaÍs Maria [UNESP]; Siervo, Mariana Di [UNESP]; Fernandes, Nathália Maria Salvadeo [UNESP]; Mileski, Milena Montanholi [UNESP]; Nardini, Rafael Calore [UNESP]; Campos, Sergio [UNESP] (My University, 2012)
The inadequate soil use is an aggravating factor of the environmental degradation and ecological unbalance. The analysis of the use and covering of the soil, by information of Remote Sensing, constitutes a technique of great usefulness to the planning and administration of the ordered occupation and rational of the physical middle, besides making possible to evaluate and to monitor the preservation of areas of natural vegetation. This work sought to evaluate the conflicts of soil use in permanent preservation areas (PPA) in Stream Comur watershed - Botucatu (SP) through Geographical Information System and satellite image of 2009. The study area is located among the geographical coordinates 48o 23’ 04” to 48o 25’ 54” of longitude WGr. and 22o 44’ 42” to 22o 48” 12” of latitude S with an area of 1,719.6 ha. The results allowed to verify that the geoprocessing techniques were of fundamental importance in the identification of the areas of soil use, of APP and of conflicts among use and PPA where it leaves of the areas of APP is being used inadequately. In terms of environmental sustainability, it can be deduced that the watershed is very unfavorable, once it presents 70.67% of area used inadequately with sugarcane and pasture.

O uso inadequado do solo é um fator agravante da degradação ambiental e desequilíbrio ecológico. A análise do uso e cobertura do solo, mediante informações de Sensoriamento Remoto, constitui uma técnica de grande utilidade ao planejamento e administração da ocupação ordenada e racional do meio físico, além de possibilitar avaliar e monitorar a preservação de áreas de vegetação natural. Este trabalho visou avaliar os conflitos de uso da terra em áreas de preservação permanentes (APP) na microbacia do Córrego Comur - Botucatu (SP) através de Sistema de Informações Geográficas e imagem de satélite de 2009. A área de estudo localiza-se entre as coordenadas geográficas 48º 23’ 04” a 48º 25’ 54” de longitude WGr. e 22º 44’ 42” a 22º 48’ 12” de latitude S com uma área de 1719,6 ha. Os resultados permitiram verificar que as técnicas de geoprocessamento foram de importância fundamental na identificação das áreas de uso de terra, de APP e de conflitos entre uso e APP onde parte das áreas de APP está sendo usada inadequadamente. Em termos de sustentabilidade ambiental, pode ser deduzido que a microbacia é muito desfavorável, uma vez apresenta 70,67% de área usada inadequadamente com cana-de-açúcar e pastagem.
Adequability of the riparian vegetation of the Stream Comur watershed at Botucatu (SP) according to environmental legislation
Keywords: Environmental legislation; Geographic information systems; APP’s; Environmental preservation; Legislação ambiental; Sistema de informação geográfica; APP’s; Preservação ambiental